Revitalisasi baca-tulis: Menumbuhkan minat literasi di tengah gangguan digital - Utami, Lukas Sri (Maliki Interdisciplinary Journal, 2023)
In an age defined by swift information streams and instantaneous entertainment, literacy, encompassing both reading and writing, might seem like a fading habit. However, the significance of literacy remains undeniable and perhaps even more pertinent in an increasingly intricate and fast-paced environment. The digital era has brought about a profound transformation in the way we interact with information and the world around us. Nevertheless, the positive impacts of technology have also presented new challenges, particularly concerning the interest and skills associated with literacy. In a world saturated with digital amusements and quick-content, the acts of reading and writing often find themselves marginalized. Revitalizing the allure of reading and writing becomes paramount as we navigate the evolving dynamics of our times.